IMPLIKASI HUKUM PURA SEBAGAI BADAN HUKUM KEAGAMAAN YANG DAPAT MEMILIKI HAK MILIK ATAS TANAH (KAJIAN TERHADAP PP NO 38 TAHUN 1963 TENTANG PENUNJUKKAN BADAN-BADAN HUKUM YANG DAPAT MEMILIKI HAK ATAS TANAH) - NI LUH ARININGSIH SARI; I MADE SURADANA; AWALUDIN AWALUDIN (GANEC SWARA, 2021)
The temple as a place of worship for Hindus has a very important meaning and function for the religious life of the Indonesian people, especially the Hindu community in Indonesia. The temple also has assets in the form of land called Plaba Pura. This Pura Plaba land finances the needs of the temple in terms of religious ceremonies, including the maintenance of the temple. The lands that are the assets of this temple even have a very wide amount so that in the development of law in society so that these assets are not lost or mismanaged by the temple management, the government makes a policy by issuing Government Regulation Number 38 of 1963 concerning the Appointment of Legal Entities who can have ownership rights on land, in conjunction with SK/556/DJA/1986 dated September 24, 1986 concerning the appointment of temples as religious legal entities that can have ownership rights on land in conjunction with the letter of the Minister of Home Affairs / Head of the National Land Agency Number 520/2252 dated 27 July 2000 which stated that SK/556/DJA/1986 also applies to temples located outside the province of Bali. As with human legal subjects, even these legal entities can have rights and obligations and can also enter into legal relations (rechtbetrekking / rechtsverhouding) both between one legal entity and another legal entity as well as between a legal entity and a human person. (natuurlijkpersoon.)